CUMULATIVE PLASTIC STRAIN AND THRESHOLD STRESS OF A QUASISATURATED COMPACTED SILTY CLAY - J. T. Shahu; Yudhbir .; S. Hayashi (International Association of Lowland Technology, 2008)
The knowledge of cumulative plastic strain and stability threshold of subgrade soil under cyclic loading is of prime importance in a proper design and maintenance planning of highway pavement structures and railway tracks. The soil beneath a pavement or a track usually exists under quasi-saturated conditions wherein the water voids in the soil remain continuous. Quasi-saturated specimens are essentially partially saturated at low confining pressures. However, with the increase in confining stresses, the air voids in the quasi-saturated specimens are dissolved into solution and the soil behaves like saturated material. Both monotonic and cyclic undrained triaxial tests have been carried out on quasi-saturated compacted specimens of a silty clay. The monotonic tests have been used to develop critical state soil mechanics framework for quasi-saturated behavior. The cyclic undrained behavior of quasi-saturated specimens has been then interpreted using this critical state framework. A generalized bilinear log-log model is proposed for the prediction of cumulative plastic strain with number of load cycles for fine-grained soils. Threshold stress is evaluated using both plastic strain development and pore pressure generation criteria. A generalized relationship between threshold stress ratio and plasticity index is proposed for a variety of soils at low and relatively high confining stresses.